EFEKTIVITAS MANAJEMEN RESIKO PEMBIAYAAN MUSYARAKAH MUTANAQISHAH (Studi Kasus pada Produk Kongsi Pemilikan Rumah Syariah di PT Bank Muamalat Indonesia Tbk. KCP Kolaka) - Irmawati Irmawati; Nur Rahmah; Askahar Askahar (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Bank Muamalat Indonesia is a bank financial institution whose operations are based on the Koran and Hadith with the aim of creating a sound financial or banking service system, free of usury or interest systems. The products in Bank Muamalat Indonesia have diversity, including the KPRS iB Muamalat financing product which uses two contracts, one of which is the musyarakah mutanaqishah contract.The formulation of the problem in this research is How is the implementation of musyarakah mutanaqishah financing on the Sharia Home Ownership Group product at Bank Muamalat KCP Kolaka? And how is the effectiveness of risk management implementation of musyarakah mutaqishah financing on Sharia Home Ownership Group products in overcoming problematic customer problems at Bank Muamalat KCP Kolaka? The research objectives were to determine the implementation of musyarakah mutanaqishah financing on the Sharia House Ownership Group product at Bank Muamalat KCP Kolaka, and to determine the effectiveness of risk management implementation of Musyarakah mutanaqishah financing on Sharia Home Ownership Collections products at Bank Muamalat KCP Kolaka.The research method used is a descriptive qualitative approach, the location and time of the study is at Bank Muamalat KCP Kolaka. While the research instrument used observation guidelines, interview guidelines and documentation guidelines. The data analysis techniques are data reduction, data triangulation, data display, and data verification and conclusion drawing.The results showed that employees and customers related to risk management of Musyarakah Mutanaqishah financing for Sharia House Ownership Collections were effective in overcoming problems faced by customers related to efforts to own houses and shop houses. This is proven through risk management at Bank Muamalat. Includes risk management for customers operational risk, marketing risk and competition risk